Factors affecting the working hours of child laborers in Dagupan City, Philippines - Ong, Michel Danica B. (Animo Repository, 2016)
Drawing on the survey conducted to 134 respondents gathered through snowball sampling, this study examines the factors that affect the working hours of child laborers (5-17years old) in the pantalan (Filipino term for fish port) of Dagupan City, Pangasinan, Philippines. The data gathered were processed through the Ordinary Least-Squares (OLS) method and were cured using the Weighted Least-Squares (WLS) due to the presence of heteroskedasticity. Results show that the average hours worked by a child laborer in a week is 28 hours. Also, 83 out of 134 respondents are male. Among the explanatory variables, household expenses, household size, gender, schooling, and child’s wage appeared to be statistically significant and affect the variation in the length of time a child works per week with beta coefficients of 0.002, 1.33, -3.1, -0.54, and -0.074 respectively. On the contrary, parental income and child’s age are shown to be statistically insignificant.